Boriding of High Chromium Steels - I. Dybkov, Vasyl (Current Physical Chemistry, 2016)
Two boride layers having different kinds of microstructure are formed on the surface of industrial high chromium steel (13 and 25% Cr) samples during their interaction with boron powder at 850–950ºC and reaction times 3600–43200 s (1–12 h). In the case of 13% Cr steel, the outer layer bordering boron consists of the FeB phase, whereas the inner layer adjacent to the solid substrate consists of the Fe2B phase. Each layer is a homogeneous phase. It is a microstructure of the first kind. With 25% Cr steel, each of boride layers is two-phase. The outer layer comprises the FeB and CrB phases, while the inner layer the Fe2B and Cr2B phases. It is a microstructure of the second kind. Both boride layers on both steels are characterized by a profound texture. Growth kinetics of boride layers obeys a parabolic relation. Boride layers with the microstructure of the second kind exhibit a much higher dry abrasive wear resistance than those with the microstructure of the first kind.
Keywords: wear resistance